Mathematical modeling of biological systems. - Deutsch, Andreas, ....-; Brusch, Lutz, ....-; Byrne, Helen, ....- (Boston : Birkhäuser, 2007)
Volume I of this two-volume, interdisciplinary work is a unified presentation of a broad range of state-of-the-art topics in the rapidly growing field of mathematical modeling in the biological sciences. Highlighted throughout the work are mathematical and computational approaches to solving central problems in the life sciences, ranging from the organizational principles of individuals cells to the dynamics of large populations. The chapters are thematically organized into the following main areas: Cellular Biophysics; Regulatory Networks; Developmental Biology; Biomedical Applications; and, Data Analysis and Model Validation. The work will be an excellent reference text for a broad audience of researchers, practitioners, and advanced students in this rapidly growing field at the intersection of applied mathematics, experimental biology and medicine, computational biology, biochemistry, computer science, and physics.
2: Epidemiology, evolution and ecology, immunology, neural systems and the brain, innovative mathematical methods and education.
Keywords: Biomedische technieken; Celbiologie; Toegepaste statistiek